(untitled) (American Journal of Islam and Society, 2012)
For anyone interested in researching herbs mentioned in the religious texts of Islam, the Encyclopedia of Islamic Herbal Medicine by John Morrow offers an abundance of information and insights. By combining information gleaned from the Qu’rān and the Sunnah, as well as the sacred writings of the Twelve Imams, Morrow proposes an authoritative reference to Prophetic medicine ‒ medicine based solely on the religious texts of Sunni and Shīʻah Islam ...